2013
DOI: 10.1371/journal.pone.0082688
|View full text |Cite
|
Sign up to set email alerts
|

Lupeol Is One of Active Components in the Extract of Chrysanthemum indicum Linne That Inhibits LMP1-Induced NF-κB Activation

Abstract: We have previously reported that seventy percent ethanol extract of Chrysanthemum indicum Linne (CIE) strongly reduces Epstein-Barr virus (EBV)-transformed lymphoblastoid cell line (LCL) survival by inhibiting virus-encoded latent infection membrane protein 1 (LMP1)-induced NF-κB activation. To identify an active compound(s) in CIE that inhibits LMP1-induced NF-κB activation, activity-guided fractionation was employed. The CH2Cl2 fraction of CIE strongly reduced LMP1-induced NF-κB activation and LCL viability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The findings are congruent with prior research which demonstrated that Chrysanthemum indicum helps to alleviate and decrease oxidative stress and inflammation [ 28 ]. Studies have also revealed that Chrysanthemum indicum has an inhibitory role on inflammation in particular NF- κ B activation in HeLa cells [ 29 ] as well as lipopolysaccharide-induced RAW 264.7 macrophages [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings are congruent with prior research which demonstrated that Chrysanthemum indicum helps to alleviate and decrease oxidative stress and inflammation [ 28 ]. Studies have also revealed that Chrysanthemum indicum has an inhibitory role on inflammation in particular NF- κ B activation in HeLa cells [ 29 ] as well as lipopolysaccharide-induced RAW 264.7 macrophages [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance and propagation of primary human foreskin fibroblast (HFF) and HEK293T cells were described previously ( Stinski, 1976 ; Kang et al, 2013 ). Recombinant lentiviral and retroviral vectors were generated by using Lenti-X TM lentiviral expression system and retroviral gene transfer and expression system, respectively, according to the manufacturer’s directions (Clontech).…”
Section: Methodsmentioning
confidence: 99%
“…The extract was re-suspended in distilled water and successively fractionated using a series of solvents, including n -Hexane, dichloromethane (CH 2 Cl 2 ), ethyl acetate (EtOAc), n -butanol (n-BuOH) and ddH 2 O (Fig. 1 ) [ 13 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%